Integration model of development of the European management consulting market - Vergunenko, Natalia (Wydawnictwo Uniwersytetu Rzeszowskiego, 2014)
The research deals with the analysis of the main trends on the European consulting market through the understanding of the structural and dynamic changes in the last years. Such analysis in this area makes it possible to draw the conclusions on the state and the development level of the economy as a whole, as well as on the interdependence of the consulting market and the GDP of European countries. Demand for the certain consulting services reflects indirectly the level of the management of the individual economic actors and the efficiency of the socio-economic structure of the country. Author characterizes the dependence between the size of MC market and the GDP of European countries with a help of the correlation models, based on the last statistical reports. The proposed models also provide a methodological basis for forecasting the main trends in the consulting industry on the global and European markets.

W artykule omówiono problem głównych trendów zachodzących w europejskim rynku konsultingowym poprzez analizę strukturalnych i dynamicznych zmian widocznych w ostatnich latach. Analiza ta umożliwia wyciągnięcie wniosków dotyczących poziomu rozwoju gospodarczego państw oraz wzajemnej zależności między poziomem PKB krajów europejskich a zaawansowaniem rynku doradztwa. Popyt na pewne usługi konsultingowe pośrednio odzwierciedla poziom zarządzania poszczególnych podmiotów ekonomicznych oraz efektywność struktury społeczno-ekonomicznej państwa. Zbadano zależności między rozwojem rynku doradztwa oraz poziomem PKB poprzez modele korelacji. Zaproponowane modele mogą służyć za metodologiczną bazę prognozowania głównych trendów zachodzących na europejskim i globalnym rynku konsultingowym.
Keywords: consulting market; management; correlation models; rynek doradztwa; zarządzanie; modele korelacji